1996
DOI: 10.1016/0895-7061(96)00031-3
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular structural and functional characteristics in patients with renovascular hypertension, primary aldosteronism and essential hypertension

Abstract: To investigate the effect of different etiologies of hypertension on left ventricular structure and function, we compared echocardiographic findings in 10 patients with renovascular hypertension (35 +/- 9 years), 10 patients with primary aldosteronism (42 +/- 9 years), and 14 patients with essential hypertension (41 +/- 6 years). There were no significant differences among the three groups in age, sex, body surface area, blood pressure, interventricular septal thickness, posterior wall thickness, left ventricu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 35 publications
3
24
0
2
Order By: Relevance
“…17,18 Compared with BP-matched primary (essential) hypertensive patients, those with PA have an excess LVH and a LV mass inappropriately high for the degree of LV workload and BP elevation. [2][3][4]9,[19][20][21][22][23][24][25][26][27][28] Cardiac fibrosis with ensuing altered LV diastolic dysfunction can lead to left atrium dilatation and increased risk of atrial fibrillation (AF) 7,8,29 ; whether these changes regress with specific treatment for PA remains uncertain. 3,4,19,20,26 We, therefore, set out to prospectively investigate the long-term effects of correction of hyperaldosteronism on BP, LV mass, and cardiovascular events in a large cohort of patients with PA.…”
mentioning
confidence: 99%
“…17,18 Compared with BP-matched primary (essential) hypertensive patients, those with PA have an excess LVH and a LV mass inappropriately high for the degree of LV workload and BP elevation. [2][3][4]9,[19][20][21][22][23][24][25][26][27][28] Cardiac fibrosis with ensuing altered LV diastolic dysfunction can lead to left atrium dilatation and increased risk of atrial fibrillation (AF) 7,8,29 ; whether these changes regress with specific treatment for PA remains uncertain. 3,4,19,20,26 We, therefore, set out to prospectively investigate the long-term effects of correction of hyperaldosteronism on BP, LV mass, and cardiovascular events in a large cohort of patients with PA.…”
mentioning
confidence: 99%
“…Hypertension caused by this frequent endocrine disorder has been shown to be associated with a higher LV mass compared to that in essential hypertension, [14][15][16] although this finding has not been supported by all authors. 17,18 These discrepancies can possibly be explained by the diversity of the studied cohorts with different severity and duration of hypertension, and different treatment or sex-related variations among the patients involved. Experimental animal studies have proposed that the excess of aldosterone can induce extracellular matrix and collagen deposition, 31 especially in the presence of high dietary salt intake.…”
Section: Discussionmentioning
confidence: 99%
“…13 Many echocardiographic studies reported a higher LV mass [14][15][16] and more frequent LV hypertrophy, although these findings are not supported by all authors. 17,18 Our recent results have also indicated an enlargement of the LV cavity and a higher prevalence of eccentric hypertrophy in PA 19 patients, suggesting the predominant effect of aldosteroneinduced increase in plasma volume and therefore the preload of the LV. Nevertheless, the exact mechanisms of the development of myocardial remodelling caused by aldosterone remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, in concordance with animal models, most of the previous clinical studies have confirmed more severe LV hypertrophy in patients with high aldosterone status, 4,6-8 although aldosterone-induced hypertrophy was not proven by all of the authors. 9,10 With the largest cohort of PA patients, Muiesan et al 6 found that high aldosterone levels could contribute to the increase of LV mass in excess of the amount needed to compensate for hemodynamic load and therefore developed more LV hypertrophy. However, the duration of hypertension, which could affect the results, was not mentioned and previous antihypertensive therapy remained unclear.…”
Section: Mass In Pamentioning
confidence: 99%
“…5 When compared with essential hypertension at the same blood pressure level, patients with PA have been considered to have greater left ventricular mass, [6][7][8] although the evidence remains controversial and is not supported by all authors. 9,10 However, it is possible that the heterogeneity of results among studies dealing with LV anatomy in patients with PA and essential hypertension (EH) might be related to the different selection criteria and characteristics of the various cohorts.…”
Section: Introductionmentioning
confidence: 99%